The Effect of Structural Reforms: Do They Differ between GDP and Adjusted Household Disposable Income? - Jamila Botev; Balázs Égert; David Turner (Center for Economic Studies and ifo Institute (CESifo), 2022)
The paper considers whether structural reforms have a different impact on adjusted household disposable income (AHDI) compared to GDP, particularly given that while the latter is currently used as the basis for the OECD Economics Department's framework for evaluating the effect of structural policy reforms, the former is arguably a better measure of welfare. The main findings are that there are indeed a number of structural policies where the long-run effects on GDP and AHDI are proportionately different, so that percentage changes in the two aggregates are significantly different following a policy reform. One group of structural policies, typically those where the transmission mechanism depends mainly on productivity and capital intensity (including cuts in corporate income tax and policies to simulate business R&D) or which can weaken the bargaining power of labour (for example a loosening of EPL), have weaker long-run positive effects on AHDI than GDP. Other structural reform policies (including in-kind family benefits, family cash benefits and cuts in the income tax wedge) have a magnified effect on AHDI, so that following a policy reform, long-run percentage changes in AHDI are larger than for GDP. Cross-referencing the analysis in the paper with structural reform priorities previously identified in the OECD's regular Going for Growth surveillance exercise, suggests that increased spending on childcare and early childhood education might usefully be part of any policy package to address the 'cost of living crisis' currently being faced by many OECD households.
Keywords: D24; E17; E24; E25; J08; 330; household disposable income; structural reforms; childcare; early childhood education; in-kind family benefits; tax wedge; employment; productivity